Multiply.
(x + 2)(x - 4)
x represents something

Question

Asked 7/7/2012 4:55:57 PM

Updated 4/27/2014 10:50:06 PM

9 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [4/27/2014 10:39:54 PM]

islandguy|Points 721|

feurem|Points 1954|

jerryjoseph002|Points 1502|

hernandezv86|Points 46|

emdroberts|Points 70|

ArslanBasit|Points 1795|

bongche|Points 2555|

chicory|Points 5481|

debnjerry|Points 33639|

johnjohn|Points 86|

jolito098|Points 353|

Expert answered|chikaygoods|Points 90|

Question

Asked 7/7/2012 4:55:57 PM

Updated 4/27/2014 10:50:06 PM

9 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [4/27/2014 10:39:54 PM]

Rating

3

(x + 2)(x - 4)

= x^2 - 4x + 2x - 8

= x^2 - 2x - 8

= x^2 - 4x + 2x - 8

= x^2 - 2x - 8

Added 4/27/2014 10:39:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:04 PM]

3

(9m + 10)*2 = 18m + 20

Added 4/27/2014 10:40:08 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:08 PM]

3

-9x^4*(5x - 2) = -45x^5 + 18x^4

Added 4/27/2014 10:41:02 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:06 PM]

3

(8x^4)*(6x^3)*(-5x^6) = -240x^13

Added 4/27/2014 10:42:00 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/27/2014 11:01:25 PM]

3

(63a)*3 = 189a

Added 4/27/2014 10:43:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:09 PM]

3

(-9)*0 = 0

Added 4/27/2014 10:44:05 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:10 PM]

3

(3x^3 + 2x^5 - 1 + 7x^4) - (5 + 9x^4 + 9x^5 - 5x^3)

= 3x^3 + 2x^5 - 1 + 7x^4 - 5 - 9x^4 - 9x^5 + 5x^3

= 8x^3 - 2x^4 - 7x^5 - 6

= 3x^3 + 2x^5 - 1 + 7x^4 - 5 - 9x^4 - 9x^5 + 5x^3

= 8x^3 - 2x^4 - 7x^5 - 6

Added 4/27/2014 10:45:57 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:11 PM]

3

(-5 + 6x^7 + 2x^5) + (9x^7 + 5x^5 + 9)

= -5 + 6x^7 + 2x^5 + 9x^7 + 5x^5 + 9

= 4 + 15x^7 + 7x^5

= -5 + 6x^7 + 2x^5 + 9x^7 + 5x^5 + 9

= 4 + 15x^7 + 7x^5

Added 4/27/2014 10:47:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:48:45 PM]

3

when x = 4 and y = 2,

x^2 + 3y^2 + 2xy

= 4^2 + 3(2^2) + 2(4)(2)

= 16 + 12 + 16

= 28 + 16

= 44

x^2 + 3y^2 + 2xy

= 4^2 + 3(2^2) + 2(4)(2)

= 16 + 12 + 16

= 28 + 16

= 44

Added 4/27/2014 10:50:06 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [4/27/2014 10:55:47 PM]

Multiply.
(8x4)(6x3)(-5x6)
**Weegy:** The answer is -12960 **User:** Multiply.
-9x4(5x - 2) **Weegy:** If 5x - 3 **User:** Multiply.
(9m + 10)2
**Weegy:** Can you kindly clarify your question please , is Multiply. (9m + 10) x 2 or
Multiply. (9m + 10)^2 ? (More)

Question

Expert Answered

Updated 6/8/2014 3:49:40 PM

3 Answers/Comments

(8x^4)(6x^3)(-5x^6) = -240x^13

Added 6/8/2014 3:48:01 PM

This answer has been confirmed as correct and helpful.

-9x^4(5x - 2) = -45x^5 + 18x^4

Added 6/8/2014 3:48:41 PM

This answer has been confirmed as correct and helpful.

(9m + 10)^2

= (9m + 10)(9m + 10)

= 81m^2 + 90m + 90m + 100

= 81m^2 + 180m + 100

= (9m + 10)(9m + 10)

= 81m^2 + 90m + 90m + 100

= 81m^2 + 180m + 100

Added 6/8/2014 3:49:40 PM

This answer has been confirmed as correct and helpful.

27,180,436

questions answered

There are no comments.